2020
DOI: 10.1001/jamanetworkopen.2019.18681
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Additional Medical Costs Among Older Adults in Japan With a History of Childhood Maltreatment

Abstract: IMPORTANCE Childhood maltreatment can have significant consequences on health through the life course, but its association with health care costs in later life is not widely known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Childhood maltreatment, defined as any form of physical, emotional, or sexual abuse and neglect that occurs to those under 18 years of age, is thought to affect one in three children globally 1 . It is well described that childhood maltreatment can have long-term effects on health through the lifespan and is associated with the development of mental and physical well-being in adolescence 2 . A recent systematic review found that 20.0% of Chinese adolescents had suffered childhood physical abuse, 30% had suffered emotional abuse, 12% had suffered sexual abuse, 47% had suffered physical neglect, and 44% had suffered emotional neglect, respectively 3 ; indicating that childhood maltreatment has also been a major public health problem among Chinese adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Childhood maltreatment, defined as any form of physical, emotional, or sexual abuse and neglect that occurs to those under 18 years of age, is thought to affect one in three children globally 1 . It is well described that childhood maltreatment can have long-term effects on health through the lifespan and is associated with the development of mental and physical well-being in adolescence 2 . A recent systematic review found that 20.0% of Chinese adolescents had suffered childhood physical abuse, 30% had suffered emotional abuse, 12% had suffered sexual abuse, 47% had suffered physical neglect, and 44% had suffered emotional neglect, respectively 3 ; indicating that childhood maltreatment has also been a major public health problem among Chinese adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Older people who have had ACEs are more likely to experience depression and have lower subjective health ( Cheong et al, 2017 ; Tani, Fujiwara, et al, 2016 ; Tani, Kondo, et al, 2016 ), and with populations continuing to age globally, the development of public/global health interventions that can mitigate such effects in old age is especially important ( World Health Organization, 2015 ). Older people with a history of childhood maltreatment tend to have additional medical and care costs compared with those who have not had ACEs ( Bellis et al, 2019 ; Isumi et al, 2020 ), so any mitigating interventions could have important impacts in reducing healthcare costs. There is evidence that social participation in neighbourhood activities can enhance the health of older people ( Levasseur et al, 2010 ; Saito et al, 2019 ; World Health Organization, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Child abuse is also a serious child health problem in Japan and has long-term social consequences [ 19 ]. The number of child abuse consultations handled by the Child Guidance Center in FY2017 was 135,152, which was 3.3 times greater than the previous 10 years, and this number is increasing each year [ 20 ].…”
Section: Introductionmentioning
confidence: 99%